A Study on Challenges and Opportunities for Organised Food and Grocery Retailing Concerning Delhi-NCR - Sanjeev Kumar (HM Journals, 2021)
Customers’ shifting behaviours and new digital technology are transforming food and grocery retail. Food features and restrictions make logistics in this field difficult. The paper aims to study the challenges and opportunities for organised food and grocery retailing in the Delhi-NCR region of India. To get insight into the perspectives of 30 organised food and grocery stores in the Delhi-NCR area, a 15-question structured questionnaire was employed to gather primary data. The results suggest that “competition from unorganised retail” is the primary concern of conventional stores. To survive in a market like India, businesses must develop new solutions. Several new market participants have made organised retailing one of the fastest-growing and most dynamic businesses.